Construction of Coplanar Bicyclic Backbones for 1, 2, 4‐Triazole‐1, 2, 4‐Oxadiazole‐Derived Energetic Materials. Issue 55 (21st August 2021) - Cao, Wenli; Dong, Wenshuai; Lu, Zujia; Bi, Yufan; Hu, Yong; Wang, Tingwei; Zhang, Chao; Li, Zhimin; Yu, Qiyao; Zhang, Jianguo
Abstract: Combining different nitrogen‐rich heterocycles into a molecule can fine‐tune its energetic performance and physical properties as well as its safety for use in energetic materials. Here, 1, 2, 4‐oxadiazole was incorporated into 1, 2, 4‐triazole to construct new energetic backbones. 3‐(5‐Amino‐1 H ‐1, 2, 4‐triazol‐3‐yl)‐1, 2, 4‐oxadiazol‐5‐amine (5 ) was designed and synthesized. Nitramino‐functionalized N ‐(5‐(5‐amino‐1, 2, 4‐oxadiazol‐3‐yl)‐3 H ‐1, 2, 4‐triazol‐3‐yl)nitramide (6 ) and N ‐(5‐(5‐(nitramino)‐1, 2, 4‐oxadiazol‐3‐yl)‐3 H ‐1, 2, 4‐triazol‐3‐yl)nitramide (7 ) were also obtained, and two series of corresponding nitrogen‐rich salts were prepared, leading to the creation of new energetic compounds. All derivatives were fully characterized, and five of them were further confirmed by X‐ray diffraction. The theoretical calculations, energetic performance, safety, and the main decomposition gaseous products of 1, 2, 4‐triazole‐1, 2, 4‐oxadiazole‐derived energetic materials were studied. Compound 7 and its dihydroxylammonium salt (7 c ) exhibited prominent detonation performance comparable to that of RDX while possessing satisfying thermal stabilities and mechanical sensitivities. Abstract : An attractive precursor 3‐(5‐amino‐1 H ‐1, 2, 4‐triazol‐3‐yl)‐1, 2, 4‐oxadiazol‐5‐amine (5 ) with coplanar bicyclic backbone was synthesized. Two nitrated products of 5 were prepared, and a series of nitrogen‐rich energetic salts were obtained and systematically characterized. These 1, 2, 4‐triazole‐1, 2, 4‐oxadiazole‐derived energetic materials exhibited high combined nitrogen and oxygen content and outstanding enthalpies of formation along with good detonation performance and an acceptable safety profile. Among them, N ‐(5‐(5‐(nitramino)‐1, 2, 4‐oxadiazol‐3‐yl)‐3 H ‐1, 2, 4‐triazol‐3‐yl)nitramide and its dihydroxylammonium salt were screened as the most balanced energetic materials.